(3GdbjhO GdhGQOg Ydi MQjI GdbGVj GdLfGFj aj Jchjf YbjOJg (B:s (3OQGSI ebGQfI (B/s - (3SdGeg LeYg CHh SQjY YHOGddgs; (3CMeO YhV HdGd (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2018)
(3ESJKfGAG ef GdCUd GdYGe ai GdEKHGJ GdLfGFi aQV GdeTQY bjhOG Ydi MQjI GdbGVj ai Jchjf YbjOJg(B: (3h ef gPg GdbjhO eG jJYdb HeUOQ GdOdjd GdLfGFi(B: (3h GdJi JJeKd ai bGYOJi eTQhYjI GdOdjd GdLfGFi h jbjfjI GdOdjd GdLfGFi(B: (3h JHOh CgejI bGYOI eTQhYjI GdOdjd GdLfGFi ai JMbjb GdJhGRf GdefThO ai GdOYhi GdLfGFjg Hjf GdeUdMg GdYGeg ai edGMbI GdeLQe h JhbjY GdYbGH JMbjbG dEYJHGQGJ GdQOY GdYGe h GdeUdMg GdNGUg ai MeGjI GdMQjGJ h JMOjO fWGb h TQhW GdeSGS HgG(B. (3CeG bGYOI jbjfjI GdOdjd GdLfGFi aJHOh CgejJgG ai JMOjO GdEWGQ GdYGe ddCOdg GdJi jLhR ddbGVi GdLfGFi Cf jSJeO EbJfGYg efgG(B: (3h GdJi jLH Cf jchf efGWgG GdLRe h Gdjbjf(B: (3h GdPi dG jecf GdhUhd Gdjg EdG ai EWGQ eLehYg ef GdVhGHW GdJi bO JJYdb HGdOdjd GdLfGFi ChGdbGVi GdLfGFi(B: (3aVdG YeG JeGQSg eMceI GdfbV ef OhQ QbGHi Ydi Pdc GdEbJfGY(B. (3cPdc aQV GdeTQY GdLfGFi bjhOG JJYdb HcaGdI Mb GdOaGY h GdeMGceg GdYGOdg(B: (3h GdJi JJeKd ai bGYOJi GdTahjg h GdJSHjH(B: (3h JHOh CgejI bGYOI GdTahjI ai EJGMI aQUI GdehGLgg Hjf CWQGa GdOYhi GdLfGFjg h SeGY GdTghO h WQM GdCOdg ddefGbTg h GdQO YdjgG(B: (3eeG jSGYO GdbGVi ddhUhd ddMbjbg(B. (3CeG bGYOI GdJSHjH aJdbi Ydi YGJb GdbGVi GdJRGeG HGdQO Ydi GdWdHGJ GdgGeg h GdOahY GdLhgQjg GdCeQ GdPi jSGYOg Ydi GdEdeGe GdcGaj HXQha GdOYhi(B: (3h EUOGQ Mceg HCSHGH bhjg JDOi Gdjg hab bhGYO GdYbd h GdefWb(B: (3MJi dG jchf YQVg ddWYf YdjI HGdHWdGf EPGTGHg YjH ef GdYjhHs
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B2018.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI UaMGJ(B: 480 - 523.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdEKHGJ GdLfGFj s; (3eHOC MQjI GdEbfGY GdbVGFjs; (3MQjI GdbGVj GdLfGFj s; (3bGYOI eTQhYjI GdOdjd GdLfGFjs; (3Gdabg GdebGQfs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs